Changes in barley (Hordeum vulgare L. subsp. vulgare) genetic diversity and structure in Jordan over a period of 31 years. Issue 2 (15th May 2017) - Thormann, I.; Reeves, P.; Thumm, S.; Reilley, A.; Engels, J. M. M.; Biradar, C. M.; Lohwasser, U.; Börner, A.; Pillen, K.; Richards, C. M.
Abstract: In many regions of the world, the cultivation of landraces is still common, in particular in centres of crop diversity. Significant effort has been put into ex situ conservation of landraces but limited data exist on the changes in genetic diversity that occur over time in farmers' fields. We assessed temporal changes in barley landrace diversity in Jordan using seed samples collected in 1981 and 2012 from the same locations. We did not observe significant changes in the amount of genetic diversity, but samples collected in 2012 were more homogenous and less locally distinct. In two sites, we observed replacement of the old material. We observed a change in phenotype, and phenotypes were found to be more homogeneous among sites in 2012. Climate changed significantly over the study period, becoming hotter and dryer, but we did not identify any correlation between the changes in climate and genetic and phenotypic variations. While the amount of genetic diversity in terms of allelic richness and number of multi-locus genotypes has been maintained, local distinctiveness among landrace barley populations in Jordan was reduced.